Analysis of Beginning Reading Difficulties of Grade 1 Students at Muhammadiyah Kemiri Elementary School - Wahyu Budi Utami; Muflikhul Khaq; Titi Anjarini (Journal of Education Technology Information Social Sciences and Health, 2024)
This research aims to determine the difficulties in reading at the beginning of class I at Muhammadiyah Kemiri Elementary School. The type of research used in the research is analytical research using qualitative methods. The research subjects were class I of Muhammadiyah Kemiri Elementary School for the 2022/2023 academic year with a total of 22 students. Data collection techniques use observation, interviews and documentation. The instrument of this research is a data card. The data obtained are student response tests and observations of learning implementation. Data analysis using reading fluency or lack of fluency. The data analysis techniques used are data collection, data reduction, data presentation and data verification. Validation of this instrument is carried out by ticking (√) in the (Fluent) column for appropriate syllables and marking (X) in the (Not Fluent) column for inappropriate syllables, then the appropriate syllables will be written in the column suggestion. The results of the validation of the performance assessment instrument to measure students' initial reading abilities are that the instrument is suitable for use with revisions.